Association Between Tobacco Chewing Habits and Leukoplakia in Low Income Urban Communities - Farah Shakeel, Naqshe Maheen, Muhammad Wahid Saleem, Menaal, Muhammad Azhar Khan, Sarah Waheed Butt, Jarin Tasnim, Ankita Poudel, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chewable tobacco remains endemic in many South-Asian low-incomeurban communities and is strongly implicated in the pathogenesis of oral potentially malignant disorders, particularly leukoplakia